2011
DOI: 10.3928/01477447-20110526-04
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Evaluation of Open Suture Anchor Fixation Versus Interference Screw for Biceps Tenodesis

Abstract: Biceps tenodesis provides reliable pain relief for patients with biceps tendon abnormality. Previous cadaver studies have shown that, for biceps tenodesis, an interference screw provides biomechanical strength to failure superior to that of suture anchors. This finding has led some providers to conclude that screw fixation for biceps tenodesis is superior to suture anchor fixation. The purpose of the current study was to test the hypothesis that the strength of a 2-suture-anchor technique with closing of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 18 publications
1
19
1
Order By: Relevance
“…1,10,23 Use of a tenodesis technique may also avoid the biceps muscle-belly cramping that is associated with tenotomy. 1,21 Many authors have described open techniques 8,19,24,27,29 as well as all-arthroscopic techniques for biceps tenodesis. 2,4,13,14,25,32 In a biomechanical assessment of 4 tenodesis techniques (open subpectoral bone tunnel biceps tenodesis, arthroscopic interference screw technique, open subpectoral interference screw fixation technique, and arthroscopic suture anchor tenodesis), there was no statistically significant difference in the ultimate failure strength among any of the techniques tested.…”
mentioning
confidence: 99%
“…1,10,23 Use of a tenodesis technique may also avoid the biceps muscle-belly cramping that is associated with tenotomy. 1,21 Many authors have described open techniques 8,19,24,27,29 as well as all-arthroscopic techniques for biceps tenodesis. 2,4,13,14,25,32 In a biomechanical assessment of 4 tenodesis techniques (open subpectoral bone tunnel biceps tenodesis, arthroscopic interference screw technique, open subpectoral interference screw fixation technique, and arthroscopic suture anchor tenodesis), there was no statistically significant difference in the ultimate failure strength among any of the techniques tested.…”
mentioning
confidence: 99%
“…Papp et al, 46 in a biomechanical study in cadavers, assessed the maximum tensile strength of two methods of open LHB tenodesis fixation: interference screw and two metal anchors associated with the repair of the transverse ligament. In both techniques, the LHB fixation was performed in the groove.…”
Section: Resultsmentioning
confidence: 99%
“…It is also suggested that LHB procedures should not be routinely indicated for the treatment of rotator cuff injuries. The main techniques described for the surgical treatment of LHB disorders were: acromioplasty, debridement, reconstruction of the biceps reflection pulley, tenotomy, and tenodesis 4, 5, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, it is likely that the postoperative patient in a sling generates cyclic loading conditions far lower than those tested by various investigators. [6][7][8][9][10][11][12][13] Frank et al 1 reported greater elongation for the suture anchor constructs than interference screw fixation. The advantage of construct stiffness is tempered by 2 negatives: early tendon tearing during cyclic testing and the creation of a torsional stress riser.…”
Section: See Related Article On Page 1760mentioning
confidence: 99%